Moondogs a novel - Yates, Alex 1982- (New York Doubleday, 2011)
Mourning the recent loss of his mother, twentysomething Benicio--aka Benny--travels to Manila to reconnect with his estranged father, Howard. But when he arrives his father is nowhere to be found--leaving an irritated son to conclude that Howard has let him down for the umpteenth time. However, his father has actually been kidnapped by a meth-addled cabdriver, with grand plans to sell him to local terrorist as bait in the country's never-ending power struggle between insurgents, separatists, and "democratic" muscle.
Keywords: Fathers and sons -- Fiction; Kidnapping -- Fiction; Americans -- Philippines -- Fiction; Insurgency -- Philippines -- Fiction; Philippines -- Fiction; Suspense fiction